Investigation of atmospheric pressure leaching conditions and leaching kinetics in the obtaining of industrial copper (II) acetate solution from copper slags - Sari, Zeynel Abidin; Turan, M. Deniz (Journal of Central South Univ, 2023)
Although many technologies have been introduced to recover valuable metals from copper slags, their economic and environmental compatibilities were not satisfactory. The dissolution behaviors of metals from copper slag, were investigated at atmospheric pressure using hydrogen peroxide and acetic acid known as organic acid. The slag was a mixture of converter and flash furnace slag containing 6.74% Cu, 4.34 % Zn and 36.45% Fe. Conventional leaching experiments in atmospheric pressure were conducted in a 100 mL glass beaker using a teflon coated magnetic stirring bar in the magnetic stirrer. Under the optimum leaching conditions, the metal extractions of 98.04 % Cu, 28.8% Zn, and 2% Fe were obtained. The Raman spectroscopy revealed the presence of coordination of Cu2+/Zn2+ with AcO- (acetate). The dissolution process was described by the first order kinetics equation. The apparent activation energy of 23.7 kJ/mol suggested that the dissolution process was under diffusion control. The reaction orders for H2O2 and CH3COOH were established to be 1.24 and 0.1, respectively. The proposed new hydrometallurgical process method is simple, environmentally friendly and remarkably superior to other methods in terms of obtaining copper (II) acetate solution from copper slag under conventional conditions.
Keywords: copper slag; copper (II) acetate solution; selective leaching; hydrogen peroxide; acetic acid